Konstrukcja i jej odbicie w strukturze przestrzenno-liturgicznej świątyni - Musiuk, Adam (Elpis, 2014)
This article presents examples of creating of Christian church architecture based on creating sacred spaces in such way to enclose in it the symbolism of the church. On the basis of these examples, the analysis of construction of the temples was carried out. It indicates that architectural solutions based on theological symbols are also the best solution in mechanics of structures. Only its precise adaptation allows to build a perfect church, both in theological and architectural aspects. It turns out that architectural and liturgical forms of the temple depend on the construction – it is a “reflection” in a terms of space and liturgy of a church, the principles of physics which means lows of nature established by God.